Simulação de escoamentos em turbinas eólicas tipo Savonius - Silva, Mylena Carvalho (2025)
Wind energy represents a significant portion of Brazil’s energy matrix, with strong growth projections for the coming years. Among wind turbine models, vertical-axis turbines are characterized by low noise levels and independence from wind direction. In particular, Savonius turbines, which feature a distinctive S-shaped rotor, exhibit good self-starting capabilities. This study aims to numerically and computationally model the behavior of a Savonius rotor under free rotation. The IMERSPEC numerical methodology is employed, which couples the Fourier pseudospectral method (FPM) with the Immersed Boundary Method (IBM). The analysis begins with the validation of the methodology for flow over square and triangular cross-section cylinders, in both fixed and flow-induced rotation conditions, reproducing wake patterns and aerodynamic coefficients consistent with computational results reported in the literature. Next, the effects of convex and concave semi-cylinders are examined, highlighting differences in recirculation mechanisms and wake structures. The fixed Savonius rotor is analyzed at different azimuthal angles, revealing that the configuration θ = π/4 yields the highest torque, whereas θ = 3π/4 is the only one to produce negative torque, due to the shading of the advancing blade. Finally, free rotation is investigated for Re = 100 and Re = 800, where two distinct regimes are identified: low-amplitude rotation and continuous rotation, respectively. In the low-amplitude regime, a direct relationship is observed between torque and azimuthal displacement, characterizing an in-phase regime, with a 2S-type wake. In the continuous rotation regime, the angular velocity increases and reaches a steady state, forming an S+P-type wake. The results confirm the applicability of the IMERSPEC methodology for modeling vertical-axis wind rotors and offer relevant contributions to the understanding of the fluid dynamic mechanisms associated with the Savonius rotor.